The point radiation defects in Li₆YB₃O₉:Eu³⁺ single crystals - Yavetskiy, R.P. (Functional Materials, 2008)
The point radiation defects in Li₆YB₃O₉:Eu³⁺ single crystals have been studied. The irradiation of Li₆YB₃O₉:Eu³⁺ single crystals with beta particles has been found to cause a valence state change (Eu³⁺ -> Eu²⁺) in some fraction of europium ions being detected by decrease of Eu³⁺ photoluminescence integral intensity, as well as formation of O⁻ hole centers resulting in appearance of a radiation induced broad absorption band in the λ = 320-500 nm range. Two models of hole centers in Li₆YB₃O₉:Eu³⁺ crystals (O⁻ isolated ion or BO₃²⁻ complex ion) have been proposed. Розглянуто точкові радіаційні дефекти у монокристалах Li₆YB₃O₉:Eu³⁺. Встановлено, що опромінення монокристалів Li₆YB₃O₉:Eu³⁺ бета-частинками спричиняє зміну валентного стану частини іонів європію Eu³⁺ -> Eu²⁺, що проявляється у зниженні інтегральної інтенсивності фотолюмінесценції іонів Eu³⁺, а також утворення діркових O⁻ центрів, що викликає появу широкої полоси індукованого оптичного поглинання в області довжин хвиль λ = 320-500 нм. Запропоновано дві моделі діркового центру у кристалах Li₆YB₃O₉:Eu³⁺: ізольований іон O⁻ або комплексний BO₃²⁻ іон. Изучены точечные радиационные дефекты в монокристаллах Li₆YB₃O₉:Eu³⁺. 'Установлено, что облучение монокристаллов Li₆YB₃O₉:Eu³⁺ бета-частицами приводит к изменению зарядового состояния части ионов европия Eu³⁺ -> Eu²⁺, фиксируемого по снижению интегральной интенсивности фотолюминесценции ионов Eu³⁺, а также к формированию дырочных O⁻ центров, что вызывает появление широкой полосы наведенного оптического поглощения в области длин волн λ = 320-500 нм. Предложены две модели дырочного центра в кристаллах Li₆YB₃O₉:Eu³⁺: изолированный ион O⁻ или комплексный BO₃²⁻ ион.